The design of safe transmission system by sets of automatically variation key information - Huo, Yingjie; Huang, Haolin; Isaeva, Gulmira; Huang, Wenya (Edelweiss Applied Science and Technology, 2025)
It’s often found in the internet that the cryptosystem can be divided into two parts, symmetric encryption system and asymmetric encryption system. The key which is used in the cryptosystem is a fixed set recently, but there are deficiencies in security. If someone try to crack the code, it is easy to make the key unsafe after a long time that resulting in the secret information leakage. The experiment was carried out using Matlab mathematics software by elliptic curve cryptography, and, tested through ZigBee facilities of the wireless transmission systems. The purpose of this paper is to project that based on the original construct which does not break the cryptosystem. We can increase the safety and do not increase the extra computed complexities. The concept in this paper is that the original used key can change automatically in server, and produces lots of sets at once. The original used key can change automatically in server, and produces lots of sets at once in this paper. Therefore, the cryptosystem can be used for long. When we transmit the information every time, the changing key will increase the difficulties that may be cracked every time. We can increase the safety and do not increase the extra computed complexities. If there is someone trying to crack the code, it is easy to make the key unsafe after a long time, resulting in the secret information leakage. Therefore, the cryptosystem can be used for long, and when we transmit the information every time, the changing key will increase the difficulties that may be cracked every time. The time and security of this cryptographic system were tested on the wireless transmission device Zigbee. The security is 15 times higher than the original mechanism when the time is longer acceptably.